(untitled) - Jones, Betty Davis (Clifton Park, NY, 2008)
This book introduce medical terminology,The terminologies in this books are organized by body system and specialty areas of practice, emphasis is placed on anatomy and physiology, pathological conditions, and diagnostic techniques and procedures. The study of word parts, the foundation of medical terminology, is integrated into every chapter, which leads to strong comprehension
Keywords: Medicine,Medicine,Y học,Y học